Users' perception on library staff attitude in Perpustakaan Tun Abdul Razak, Universiti Teknologi Mara / Kasmarini Baharuddin - Baharuddin, Kasmarini (2011)
This study investigates users' perception on the performance of library staff attitude in an academic library, which is the Perpustakaan Tun Abdul Razak (PTAR), Universiti Teknologi MARA (UiTM) Shah Alam. The library staff in PTAR 1 and PTAR 2 were assessed based on their attitude in terms of reliabilty, responsiveness and assurance. Questionnaires were distributed to 150 respondents of whom 140 (93%) responded. Descriptive and inferential statitistics were used in the analysis of data using Statistical Product Service and Solution (SPSS). The results revealed that the overall mean scores of users' perception on library staff attitude by dimension of reliability was 3.33, the overall mean scores by dimension of responsiveness was 3.30 and the overall mean scores by dimension of assurance was 3.43. The highest mean of the reliability dimension is library staff are able to give the right answers to users' question (mean=3.52), followed by the dimension on responsiveness which was library staff are ready to respond to users' questions (mean=3,47) while for the highest mean for the dimension on assurance was a two way communication between a library staff and users are very important to make sure that users will come to the same library again in the future (mean=3.75). Majority (75 or 53.6%) of the respondents indicated that they use the library services quite frequently. Only a small number (13 or 9.3%) use the library very frequently. The most common problems faced by them were library staff did not give enough attention, followed by lack of number of staffs to entertain users and lack of communication skill The study shows that there was a significant difference on the perceptions on library staff attitude regarding reliability from both different faculties which are Faculty of Law and Faculty of Accountancy. Respondents perceived different perceptions towards library staff attitude regarding reliability. In terms of the relationship between perceptions regarding reliability and usage of library services, the correlation coefficient was 0.246, responsiveness and usage of library services was 0.199 while assurance and usage of library services was 0.183. The researcher hopes that the findings of this study will contribute positively towards excellent library services. The study had a profound impact on making recommendations to all types of libraries concerned with library services in giving the best services to library users and also in ensuring the library staff to work efficiently and effectively at all times.